Flexural Strength Analysis of Laminated Composites Using Clam Shell Powder and Bagasse Powder - Ramadani Siregar; Zainal Arif; Muhammad Zulfri; Syamsul Bahri Widodo; Nazaruddin Abdul Rachman (Fakultas Teknik Universitas Samudra, 2023)
Composites are materials that have specific properties based on their constituent materials. The constituent materials consist of binders and reinforcements. Reinforcing materials come from synthetic fibers and natural fibers. Natural fibers can be waste that is wasted in the environment. These wastes include bagasse waste and clam shells. These wastes are made into fibers. Resin is mixed with fiber and blowing agent, then stirred until evenly distributed and poured into the mold, resulting in a composite material. This study aims to obtain the strength of composite materials due to three-point bending loading with the laminate fiber layer method. The manufacture of this test specimen uses bagasse powder and clamshell powder formed with a casting system. This material consists of 4 layers. The first and third layers are clamshell powder, and the second and third layers are bagasse powder. The fiber sizes of the specimens are 300mesh, 400mesh, and 500mesh. The fiber fraction ratio was 10% and 15%. The models were laminated and tested for three-point bending. The best results were found in the 500 mesh fiber size specimen, with a fraction ratio of 85% resin and 15% clam shell powder and bagasse. The maximum stress obtained was 63.46 MPa and strain 0.59 mm, with a bending force of 487.42 N.